Degradable medical itaconic acid polyurethane material as well as preparation method and application thereof

By using medical itaconic acid polyurethane materials prepared by using bio-itaconic acid and polyester glycol, the problem of existing polyurethane materials lacking degradability and biocompatibility in the medical field is solved, and high performance and environmental protection are achieved. Medical polyurethane material.

CN119409934AActive Publication Date: 2025-02-11NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411536699.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-11
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

Existing polyurethane materials lack degradability and good biocompatibility in the medical field, and their design ideas rely on petroleum-based raw materials, which have problems of environmental pollution and resource shortage.

Method used

Using itaconic acid from bio-based sources and polyester glycol as the soft segment structure of polyurethane, medical icon with degradable properties, excellent mechanical properties, stable thermodynamics and good biocompatibility are prepared through esterification and polycondensation reaction. Acid polyurethane material.

Benefits of technology

The degradability and biocompatibility of polyurethane materials are achieved, and the comprehensive performance is no less than that of pure commercial soft-segment polyurethane materials. At the same time, it reduces adverse reactions such as bioadhesion, providing a new strategy for biodegradable medical implanted polyurethane materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409934A_ABST
    Figure CN119409934A_ABST
Patent Text Reader

Abstract

The invention discloses a degradable medical itaconic acid polyurethane material as well as a preparation method and application thereof. The degradable medical itaconic acid polyurethane material has the following structure: # imgabs0 # R1 is a residue of a hydroxyl-terminated itaconic acid diol oligomer, R2 is a residue of polyester diol, D is a residue of diisocyanate, B is a residue of straight-chain dihydric alcohol, and n is a positive integer from 5 to 12. The preparation method comprises the following steps: carrying out esterification reaction and polycondensation reaction on itaconic acid, short-chain dihydric alcohol, a polymerization inhibitor and a first catalyst to prepare a hydroxyl-terminated itaconic acid diol oligomer; carrying out microwave prepolymerization reaction on the itaconic acid polyurethane material, polyester diol, diisocyanate, a solvent and a second catalyst, and adding straight-chain dihydric alcohol to continuously carry out chain extension reaction, so as to prepare the degradable medical itaconic acid polyurethane material. The itaconic acid polyurethane material prepared by the preparation method disclosed by the invention has the advantages of degradability, excellent mechanical property, stable thermodynamics and good biocompatibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of bio-based polymer materials, and specifically relates to a degradable medical itaconic acid polyurethane material and a preparation method and application thereof. Background Art

[0002] Polyurethane, also known as polyurethane (PU), is an important polymer compound. It is prepared by addition polymerization of diisocyanate containing at least two active groups and polyol. Polyurethane has a structure containing both soft segments and hard segments, and there is a covalent bond between the soft segments and the hard segments, thus having a microphase separation structural characteristic. This feature can be used to adjust its structure appropriately by changing the soft and hard segment component structure in polyurethane or adding other fillers to obtain products with desired performance. In the 1830s, Dr. Bayer of Germany first invented polyurethane fiber (spandex fiber). After ninety years of development, new structures of polyurethane soft and hard segments have emerged in an endless stream, making polyurethane materials have a wider range of performance adjustability and more diversified product forms. Polyurethane foam, fiber, adhesive and other products are widely used in many fields such as interior decoration, road engineering and drug sustained release, showing its extensive presence in people's lives and the diversity of products.

[0003] Reasonable design of the structure of polyurethane materials can obtain polyurethane materials with good biocompatibility, and at the same time, more functions can be given to polyurethane through subsequent modification methods. CN117599260A discloses the active preparation and application of a medical polyurethane foam with anti-inflammatory function, firstly preparing polyurethane foam, then introducing particles capable of decomposing active oxygen into the foam body, utilizing in-situ reduction reaction to catalyze the decomposition of active oxygen into water and oxygen, thereby inhibiting the occurrence of inflammatory reaction, and can be applied to medical fields such as plugging, filling, and hemostasis, but it does not have certain degradable properties. CN118165190A discloses a surface functional modification method for medical polyurethane materials, firstly preparing a diisocyanate-terminated polyurethane prepolymer, then covalently grafting it with a dihydroxybenzophenone compound under light-initiated conditions to prepare a polyurethane material, so that the surface of the medical polyurethane material is functionally modified, but the matrix structure of the polyurethane does not have certain innovation.

[0004] With the popularization of the concept of "green chemistry", the design idea of ​​using petroleum-based raw materials to prepare polyurethane materials is no longer promoted. At the same time, the large-scale use of petroleum-based raw materials will cause serious environmental problems such as shortage of basic resources. Using bio-based resources to prepare polyurethane materials has become a new idea to achieve a greener and more environmentally friendly design and preparation of polyurethane structures.

[0005] Therefore, how to prepare a new technology of polyurethane material with biodegradable properties and good biocompatibility has become the direction that researchers in the industry have been working towards for a long time. Summary of the invention

[0006] The main purpose of the present invention is to provide a degradable medical itaconic acid polyurethane material and a preparation method to overcome the deficiencies in the prior art.

[0007] Another object of the present invention is to provide application of the degradable medical itaconic acid polyurethane material.

[0008] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:

[0009] The embodiment of the present invention provides a degradable medical itaconic acid polyurethane material having a structure as shown in formula (I):

[0010]

[0011] Among them, R 1 is the residue of a hydroxyl-terminated itaconic acid diol oligomer, R 2 is a residue of polyester diol, D is a residue of diisocyanate, B is a residue of straight-chain diol, and n is a positive integer between 5 and 12.

[0012] The embodiment of the present invention also provides a method for preparing a degradable medical itaconic acid polyurethane material, which comprises:

[0013] subjecting a first mixed reaction system comprising itaconic acid, a short-chain diol, a polymerization inhibitor and a first catalyst to an esterification reaction and a polycondensation reaction to obtain a hydroxyl-terminated itaconic acid diol oligomer;

[0014] A second mixed reaction system comprising itaconic acid diol oligomer, polyester diol, diisocyanate, solvent and a second catalyst is subjected to microwave prepolymerization reaction, and then a linear diol is added to continue the chain extension reaction to obtain a degradable medical itaconic acid polyurethane material.

[0015] The embodiment of the present invention also provides a degradable medical itaconic acid polyurethane material prepared by the above-mentioned preparation method.

[0016] The embodiment of the present invention also provides the use of the aforementioned degradable medical itaconic acid polyurethane material in the preparation of medical implants.

[0017] Correspondingly, an embodiment of the present invention further provides a method for preparing a vascular transplant tubular article, which comprises: preparing the vascular transplant tubular article by electrospinning the degradable medical itaconic acid polyurethane material.

[0018] Compared with the prior art, the beneficial effects of the present invention are at least:

[0019] 1) The present invention utilizes the active carboxyl structure of itaconic acid from bio-based sources to synthesize hydroxyl-terminated itaconic acid diol oligomers, and uses polyester diol as the polyurethane soft segment structure. The prepared itaconic acid polyurethane material has degradable properties, excellent mechanical properties, stable thermodynamics and good biocompatibility;

[0020] 2) The comprehensive performance of the itaconic acid polyurethane material prepared by the present invention is not inferior to that of pure commercial soft segment polyurethane material, and the material has an appropriate contact angle to reduce adverse reactions such as biological adhesion, thus proposing a new strategy for biodegradable medical implant polyurethane materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 Schematic diagram of the synthesis process of itaconic acid diol oligomer prepared in Example 1 of the present invention;

[0023] Figure 2 Schematic diagram of the synthesis process of the degradable medical itaconic acid polyurethane material prepared in Example 1 of the present invention;

[0024] Figure 3 is a tensile performance curve of the degradable medical itaconic acid polyurethane material prepared in Example 1 of the present invention;

[0025] Figure 4a and Figure 4b This is a Masson and H&E staining diagram of the tissue of the degradable medical itaconic acid polyurethane material implanted in the body for 30 days in Example 1 of the present invention;

[0026] Figure 5 is the infrared spectrum of the degradable medical itaconic acid polyurethane material prepared in Example 1 of the present invention;

[0027] Figure 6 It is a schematic diagram of the degradability of the degradable medical itaconic acid polyurethane material prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0028] In view of the problems existing in the above-mentioned prior art, after long-term research and a large number of experiments, the inventors of this case proposed a degradable medical itaconic acid polyurethane material, which is prepared using itaconic acid raw materials from biomass. The itaconic acid polyurethane material has degradable properties, excellent mechanical properties, stable thermodynamics and good biocompatibility.

[0029] Itaconic acid (IA) is one of the 12 biomass chemical substances with the highest added value announced by the U.S. Department of Energy. It has an unsaturated double bond and two carboxyl groups in its structure. It has active chemical properties and can undergo a variety of reactions such as addition, esterification, and polymerization. It also has anti-inflammatory, antibacterial, and antiviral effects. Therefore, it has great potential for use in the preparation of biomedical materials.

[0030] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0031] As one aspect of the technical solution of the present invention, a degradable medical itaconic acid polyurethane material has a structure as shown in formula (I):

[0032]

[0033] In formula (I), R 1 is the residue of a hydroxyl-terminated itaconic acid diol oligomer, R 2 is the residue of polyester diol, D is the residue of diisocyanate, B is the residue of linear diol chain extender, and n is a positive integer, and n is 5-12.

[0034] In some embodiments, the R 1 It is the residue of itaconic acid diol oligomer prepared from itaconic acid and short-chain diol.

[0035] Furthermore, the short-chain diol may include any one or a combination of two or more of 1,2-ethylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 1,5-pentanediol, 1,6-hexanediol, etc., but is not limited thereto.

[0036] In the structural formula (I), R 1 is the hydroxyl-terminated itaconic acid diol oligomer residue, R 2 The polyester part of the present invention adopts a binary soft segment structure, and introduces the itaconic acid oligomer diol part, so that the structure of the side double bond exists in the overall structure, which will change the thermodynamics and surface wettability of the material. For example, compared with polycaprolactone diol, the material of the present invention has a higher glass transition temperature and a larger contact angle.

[0037] Itaconic acid has an unsaturated double bond and two carboxyl groups, and is chemically active, and can undergo a variety of reactions such as addition, esterification, and polymerization. The active carboxyl groups of itaconic acid react with the hydroxyl groups of short-chain diols to obtain hydroxyl-terminated itaconic acid diol oligomers, which provide a structural basis for the synthesis of itaconic acid polyurethanes. The itaconic acid polyurethane material prepared using itaconic acid diol oligomers has a series of advantages such as being green, environmentally friendly, and biodegradable.

[0038] In some embodiments, R 2 Derived from polyester diol, the polyester diol may include any one or a combination of two or more of polycaprolactone diol, polyethylene glycol, polyhexamethylene adipate, etc., but is not limited thereto.

[0039] Furthermore, the number average molecular weight of the polyester diol is 500-2000.

[0040] In some embodiments, B is derived from a linear diol, which may include any one or a combination of two or more of 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, etc., but is not limited thereto. The present invention uses a linear diol, which enhances flexibility.

[0041] In some embodiments, D is derived from a diisocyanate, which may include any one or a combination of two or more of diphenylmethane diisocyanate, isophorone diisocyanate, p-phenylene diisocyanate, 1,5-naphthalene diisocyanate, toluene diisocyanate and dicyclohexyl diisocyanate, but is not limited thereto.

[0042] In some embodiments, the degradable medical itaconic acid polyurethane material includes a soft segment comprising a residue of an itaconic acid diol oligomer and a residue of a polyester diol, and a hard segment comprising a residue of a diisocyanate and a residue of a linear diol.

[0043] Furthermore, the content of the soft segment in the degradable medical itaconic acid polyurethane material is 50 to 70 wt %; when the soft segment content is higher, the product is more flexible, and the binary aliphatic long chain structure provides a certain flexibility; when the ratio of itaconic acid diol oligomer to polyester diol in the soft segment increases, its overall flexibility will decrease due to the side double bonds in the itaconic acid diol oligomer.

[0044] Furthermore, in the soft segment comprising the residue of itaconic acid diol oligomer and the residue of polyester diol, the mass proportion of itaconic acid diol oligomer is 25% to 65%.

[0045] In some embodiments, the degradable medical itaconic acid polyurethane material of the present invention has a wide adjustable range, with a tensile modulus of 5 to 80 MPa, a tensile strength of 8.0 to 33.8 MPa, and an elongation at break of 170 to 500%.

[0046] As one aspect of the technical solution of the present invention, a method for preparing a degradable medical itaconic acid polyurethane material involves:

[0047] subjecting a first mixed reaction system comprising itaconic acid, a short-chain diol, a polymerization inhibitor and a first catalyst to an esterification reaction and a polycondensation reaction to obtain a hydroxyl-terminated itaconic acid diol oligomer;

[0048] A second mixed reaction system comprising itaconic acid diol oligomer, polyester diol, diisocyanate, solvent and a second catalyst is subjected to microwave prepolymerization reaction, and then a linear diol is added to continue the chain extension reaction to obtain a degradable medical itaconic acid polyurethane material.

[0049] In some more specific preferred embodiments, the preparation method of the degradable medical itaconic acid polyurethane material comprises the following steps:

[0050] Step 1, mixing itaconic acid and a short-chain diol, adding a polymerization inhibitor and a first catalyst, preparing a hydroxyl-terminated itaconic acid diol oligomer by a two-step method of esterification and polycondensation, and performing drying treatment;

[0051] Step 2, adding polyester diol as the binary soft segment structural system to the itaconic acid diol oligomer dried in step 1, and adding diisocyanate, solvent and a second catalyst at the same time, adding linear diol after a period of microwave prepolymerization to continue the chain extension reaction to obtain the degradable medical itaconic acid polyurethane material.

[0052] In some embodiments, in step 1, the short-chain diol may include any one or a combination of two or more of 1,2-ethylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 1,5-pentanediol, 1,6-hexanediol, etc., but is not limited thereto.

[0053] The itaconic acid diol oligomer of the present invention is prepared by a solvent-free melt polycondensation method.

[0054] In some embodiments, in step 1, the polymerization inhibitor may include any one or a combination of two or more of 4-methoxyphenol, hydroquinone, o-methylhydroquinone, p-hydroxyanisole, etc., but is not limited thereto.

[0055] Further, in step 1, the first catalyst may include any one or a combination of two or more of stannous chloride dihydrate, p-toluenesulfonic acid hydrate, zinc acetate dihydrate, etc., but is not limited thereto.

[0056] In some embodiments, in step 1, the molar ratio of itaconic acid to short-chain diol is in the range of 1:1.1 to 1:1.3.

[0057] Furthermore, the amount of the polymerization inhibitor used is 0.4-0.8% of the molar amount of itaconic acid.

[0058] Furthermore, the amount of the first catalyst used is 0.1 to 0.3% of the molar amount of itaconic acid.

[0059] In some embodiments, in step 1, the temperature of the esterification reaction is 120-150° C., and the time of the esterification reaction is 8-10 h.

[0060] In some embodiments, in step 1, the temperature of the polycondensation reaction is 170-180° C., and the time of the polycondensation reaction is 1-4 hours.

[0061] In some embodiments, in step 2, the polyester diol may include any one or a combination of two or more of polycaprolactone diol, polyethylene glycol, polyhexamethylene adipate, etc., but is not limited thereto. The polyester diol is preferably polycaprolactone diol, which acts as a binary soft segment structure part in the polyurethane backbone together with itaconic acid diol oligomer.

[0062] Furthermore, the number average molecular weight of the polyester diol is 500-2000.

[0063] In some embodiments, in step 2, the diisocyanate may include any one or a combination of two or more of diphenylmethane diisocyanate, isophorone diisocyanate, p-phenylene diisocyanate, 1,5-naphthalene diisocyanate, toluene diisocyanate and dicyclohexyl diisocyanate, but is not limited thereto. The diisocyanate is preferably diphenylmethane diisocyanate, toluene diisocyanate, etc.

[0064] In some embodiments, the amount of the isocyanate is calculated based on the hydroxyl groups of the mixture of itaconic acid diol oligomer, polyester diol and linear diol, and the total isocyanate index of the system is 1.05-1.10.

[0065] In some embodiments, in step 2, the linear diol may include any one or a combination of two or more of 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, etc., but is not limited thereto.

[0066] Further, the solvent may include N,N-dimethylformamide, but is not limited thereto.

[0067] In some embodiments, in step 2, the second catalyst may include an amine compound and / or an organometallic compound, preferably including but not limited to any one or a combination of two or more of dibutyltin dilaurate, stannous octoate, tin isooctanoate, etc.

[0068] In some embodiments, in step 2, the molar ratio of the itaconic acid diol oligomer to the polyester diol is in the range of 1:2 to 2:1.

[0069] Furthermore, the amount of the second catalyst used is 1% to 2% of the total mass of the second mixed reaction system.

[0070] In some embodiments, in step 2, the mass ratio of the combination of the straight-chain diol and diisocyanate to the combination of itaconic acid diol oligomer and polyester diol is 5:5 to 7:3. In other words, the mass ratio of the straight-chain diol as a chain extender and the diisocyanate as a hard segment structure to the soft segment structure (itaconic acid diol oligomer, polyester diol) is in the range of 5:5 to 7:3.

[0071] In some embodiments, in step 2, the temperature of the microwave prepolymerization reaction is 60-70° C., and the time of the microwave prepolymerization reaction is 20-40 min.

[0072] In some embodiments, in step 2, the temperature of the chain extension reaction is 60-80° C., and the time of the chain extension reaction is 40-70 min.

[0073] Taking into account the performance of the product polyurethane, the present invention adopts a step-by-step method rather than a one-pot method to prepare the degradable medical itaconic acid polyurethane material.

[0074] Among them, in the process of preparing the degradable medical itaconic acid polyurethane material, hydroxyl-terminated itaconic acid diol oligomers, polyester diols, linear diols, etc. all need to be dehydrated before reacting.

[0075] As one aspect of the technical solution of the present invention, it involves a degradable medical itaconic acid polyurethane material prepared by the above-mentioned preparation method.

[0076] Furthermore, the present invention uses itaconic acid diol oligomer as the soft segment structure of polyurethane, and degradation and biological experimental tests prove that the prepared itaconic acid polyurethane material has degradable properties, excellent mechanical properties, stable thermodynamic properties and good biocompatibility.

[0077] As one aspect of the technical solution of the present invention, it involves the use of the aforementioned degradable medical itaconic acid polyurethane material in the preparation of medical implants.

[0078] Furthermore, the medical implant may be a vascular graft tube, but is not limited thereto.

[0079] The comprehensive performance of the itaconic acid polyurethane material prepared by the present invention is not inferior to that of pure commercial soft segment polyurethane material, and the material has an appropriate contact angle size to reduce adverse reactions such as biological adhesion, thus proposing a new strategy for biodegradable medical implant polyurethane material.

[0080] As one aspect of the technical solution of the present invention, it relates to a method for preparing a vascular graft tubular article, which comprises: preparing a small-caliber vascular graft tubular article by electrospinning the degradable medical itaconic acid polyurethane material.

[0081] Specifically, the process conditions of the electrospinning technology include: a spinning solution concentration of 20-30%, a voltage of 12-17 KV, a receiver distance of 12-18 cm, and an injection rate of 0.8-1.2 mL / h.

[0082] In summary, the present invention utilizes the active carboxyl structure of bio-based itaconic acid to synthesize hydroxyl-terminated itaconic acid diol oligomers, and uses polyester diol as the polyurethane soft segment structure. The obtained itaconic acid polyurethane material has degradable properties, excellent mechanical properties, stable thermodynamics and good biocompatibility.

[0083] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.

[0084] The raw materials used in the following specific embodiments are all purchased from the market.

[0085] Example 1

[0086] Step 1: weigh 65.1 g (0.5 mol) of itaconic acid and 50.7 g (0.56 mol) of 1,4-butanediol raw materials, add them into a three-necked flask, and add 0.24 g (0.5% mol relative to itaconic acid) of inhibitor hydroquinone to protect the double bond, and the first catalyst SnCl 2 ·2H 2 O0.2g (0.16% mol relative to itaconic acid). Pass nitrogen, install a stirring rod and a condenser, and perform esterification at 150°C for 10 hours; then remove the condenser and nitrogen, and perform polycondensation at 180°C in a vacuum for 2-3 hours. The crude product is dissolved in chloroform, and oligomers are precipitated with a large amount of methanol or ethanol. The liquid is allowed to stand and the lower layer is evaporated to remove the solvent, thereby obtaining itaconic acid butanediol oligomers. The synthesis process and product structure are shown in Figure 1 shown.

[0087] Step 2: weigh 3.13 g of itaconate butylene glycol oligomer and 4.5 g of polycaprolactone diol (n IABDo :n PCL =1:2) was placed in a straight three-necked flask, as a divalent polyol structure (only one divalent alcohol substance was weighed for the monovalent soft segment structure, 6.42g of diphenylmethane diisocyanate was used as the polyurethane hard segment structure, and the system isocyanate index was 1.1. At the same time, 70-80g of N, N-dimethylformamide was added as a reaction solvent and 0.09g of dibutyltin dilaurate was added as a second catalyst. Subsequently, the straight three-necked flask was placed in a microwave reactor, nitrogen was passed through, a mechanical stirring and condensation reflux device was installed, and a microwave prepolymerization reaction was carried out at 60°C for 30min, and then 1.21g of 1,3-propylene glycol was added, and a chain extension reaction was carried out at 70°C for 50min. After the reaction was completed, the reaction solution was poured into a tetrafluoro plate or a culture dish, and placed on a hot plate at a temperature of 70°C to volatilize the solvent to form a degradable medical itaconic acid polyurethane material. The synthesis process and product structure are shown in Figure 2 Its infrared spectrum is shown in Figure 5 shown.

[0088] The prepared itaconic acid polyurethane material was cut into dumbbell-shaped tensile specimens and tested using a universal specimen tensile machine according to the international standard ISO 527-1:2012. Figure 3 As shown, the itaconic acid polyurethane material prepared in this embodiment has a tensile modulus of 37.8 MPa, a tensile strength of 33.8 MPa, an elongation at break of 480%, and good biocompatibility.

[0089] The Masson and H&E staining images of the tissues of the degradable medical itaconic acid polyurethane material implanted in the body for 30 days in this embodiment are shown in Figures 1 and 2. Figure 4a and Figure 4b shown.

[0090] Example 2

[0091] The preparation method of Example 1 is followed, except that the hard segment Hs (total mass of isocyanate and linear diol): soft segment Ss (total mass of itaconic acid oligomer and polyester diol) = 5:5 is replaced by Hs:Ss = 6:4 to obtain an itaconic acid polyurethane material. The various properties thereof are tested by the same method as above and it is found that the obtained itaconic acid polyurethane material has a tensile modulus of 25.6 MPa, a tensile strength of 22.9 MPa, an elongation at break of 460%, and good biocompatibility. Figure 6 This is a schematic diagram of the degradability of the degradable medical itaconic acid polyurethane material prepared in this example.

[0092] Example 3

[0093] The preparation method of Example 1 is followed, except that the hard segment Hs (total mass of isocyanate and linear diol): soft segment Ss (total mass of itaconic acid oligomer and polyester diol) = 5:5 is replaced by Hs:Ss = 7:3 to obtain an itaconic acid polyurethane material. The various properties thereof are tested by the same method as above and it is found that the prepared itaconic acid polyurethane material has a tensile modulus of 16.4 MPa, a tensile strength of 9 MPa, an elongation at break of 340%, and has good biocompatibility.

[0094] Example 4

[0095] The preparation method of Example 1 is followed, except that 1 part of itaconic acid diol oligomer is replaced by 2 parts to obtain an itaconic acid polyurethane material. The various properties thereof are tested by the same method as above, and it is found that the prepared itaconic acid polyurethane material has a tensile modulus of 30.5 MPa, a tensile strength of 31.9 MPa, an elongation at break of 500%, and has good biocompatibility.

[0096] Example 5

[0097] The preparation method of Example 1 is followed, except that 1 part of N,N-dimethylformamide solvent is replaced by 0.5 parts to obtain an itaconic acid polyurethane material. The various properties thereof are tested by the same method as above and it is found that the prepared itaconic acid polyurethane material has a tensile modulus of 34.2 MPa, a tensile strength of 33.5 MPa, an elongation at break of 500%, and has good biocompatibility.

[0098] Example 6

[0099] The preparation method of Example 1 is followed, except that 1 part of N,N-dimethylformamide solvent is replaced by 1.2 parts to obtain an itaconic acid polyurethane material. The various properties thereof are tested by the same method as above and it is found that the prepared itaconic acid polyurethane material has a tensile modulus of 27.2 MPa, a tensile strength of 25.4 MPa, an elongation at break of 460%, and has good biocompatibility.

[0100] Example 7

[0101] The preparation method of Example 1 is as follows, except that: the 1,4-butanediol in the first step is replaced by 1,6-hexanediol, the molar ratio of itaconic acid to 1,6-hexanediol is 1:1.1, the amount of the inhibitor is 0.4% of the molar amount of itaconic acid, and the first catalyst SnCl 2 ·2H 2The amount of O accounted for 0.1% of the molar amount of itaconic acid, the esterification reaction was carried out at 120°C for 9 hours, and the vacuum condensation reaction was carried out at 170°C for 4 hours to obtain the itaconic acid polyurethane material. The various properties were tested using the same method as above and it was found that the prepared itaconic acid polyurethane material had a tensile modulus of 28.4 MPa, a tensile strength of 26.9 MPa, an elongation at break of 530%, and good biocompatibility.

[0102] Example 8

[0103] The preparation method of Example 1 is as follows, except that the inhibitor in the first step is changed to 4-methoxyphenol, the molar ratio of itaconic acid to 1,6-hexanediol is 1:1.3, the amount of the inhibitor is 0.8% of the molar amount of itaconic acid, and the first catalyst SnCl 2 ·2H 2 The amount of O accounted for 0.3% of the molar amount of itaconic acid, the esterification reaction was carried out at 140°C for 8 hours, and the vacuum condensation reaction was carried out at 175°C for 1 hour to obtain the itaconic acid polyurethane material. The various properties were tested using the same method as above and it was found that the prepared itaconic acid polyurethane material had a tensile modulus of 24.3 MPa, a tensile strength of 21.8 MPa, an elongation at break of 460%, and good biocompatibility.

[0104] Example 9

[0105] The preparation method of Example 1 is as follows, except that: the SnCl 2 ·2H 2 The catalyst O was changed to p-toluenesulfonic acid hydrate to obtain itaconic acid polyurethane material. The properties were tested by the same method as above and it was found that the prepared itaconic acid polyurethane material had a tensile modulus of 25.8 MPa, a tensile strength of 27.3 MPa, an elongation at break of 550%, and good biocompatibility.

[0106] Example 10

[0107] The preparation method of Example 1 is followed, except that the isocyanate in the second step is changed to dicyclohexyl diisocyanate to obtain itaconic acid polyurethane material. The various properties thereof are tested by the same method as above and it is found that the prepared itaconic acid polyurethane material has a tensile modulus of 14.9 MPa, a tensile strength of 16.2 MPa, an elongation at break of 490%, and good biocompatibility.

[0108] Embodiment 11

[0109] The preparation method of Example 1 is followed, except that the straight-chain diol in the second step is changed to 1,4-butanediol, the molar ratio of itaconic acid diol oligomer to polycaprolactone diol is 2:1, the second catalyst is tin isooctanoate, and the amount of the second catalyst is 2% of the total mass of the second mixed reaction system to obtain an itaconic acid polyurethane material. The various properties thereof are tested by the same method as above and it is found that the obtained itaconic acid polyurethane material has a tensile modulus of 28.6 MPa, a tensile strength of 30.2 MPa, an elongation at break of 520%, and good biocompatibility.

[0110] Example 12

[0111] The preparation method of Example 1 is followed, except that the isocyanate index in the second step is changed to 1.05 to obtain an itaconic acid polyurethane material. The various properties thereof are tested by the same method as above and it is found that the prepared itaconic acid polyurethane material has a tensile modulus of 26.2 MPa, a tensile strength of 23.8 MPa, an elongation at break of 440%, and good biocompatibility.

[0112] Embodiment 13

[0113] The preparation method of Example 1 is followed, except that the second catalyst in the second step is changed to stannous octoate in an amount of 1% of the total mass of the second mixed reaction system, a microwave prepolymerization reaction is carried out at 70°C for 20 minutes, and a chain extension reaction is carried out at 80°C for 40 minutes to obtain an itaconic acid polyurethane material. The various properties thereof are tested using the same method as above and it is found that the obtained itaconic acid polyurethane material has a tensile modulus of 30.1 MPa, a tensile strength of 32.9 MPa, an elongation at break of 520%, and good biocompatibility.

[0114] Embodiment 14

[0115] The preparation method of Example 1 is followed, except that the polyester diol in the second step is changed to polyethylene glycol, a microwave prepolymerization reaction is carried out at 65°C for 40 minutes, and a chain extension reaction is carried out at 60°C for 70 minutes to obtain an itaconic acid polyurethane material. The various properties thereof are tested by the same method as above and it is found that the prepared itaconic acid polyurethane material has a tensile modulus of 22.6 MPa, a tensile strength of 21.5 MPa, an elongation at break of 450%, and good biocompatibility.

[0116] Comparative Example 1

[0117] The difference between this comparative example and the preparation method of Example 1 is that: IABDo :n PCL =1:2 replaced by n IABDo :n PCL=1:3, to obtain itaconic acid polyurethane. The properties thereof were tested by the same method as above and it was found that the itaconic acid polyurethane had a tensile modulus of 12 MPa, a tensile strength of 14.3 MPa, an elongation at break of 280%, and mechanical properties were lower than those of Example 1. The reason was that the component difference ratio between polycaprolactone and itaconic acid oligomer was too large to affect the arrangement of molecular segments.

[0118] Comparative Example 2

[0119] The difference between this comparative example and the preparation method of Example 1 is that: IABDo :n PCL =1:2 replaced by n IABDo :n PCL =3:1, to obtain itaconic acid polyurethane. The properties thereof were tested by the same method as above and it was found that the itaconic acid polyurethane had a tensile modulus of 9.8 MPa, a tensile strength of 11.3 MPa, and an elongation at break of 210%. The mechanical properties were lower than those of Example 1. The reason was that the itaconic acid oligomer had a side double bond structure compared to polycaprolactone diol, which would increase certain steric hindrance. Excessive itaconic acid components would affect the connection and entanglement of the molecular chains.

[0120] Comparative Example 3

[0121] The difference between this comparative example and the preparation method of Example 1 is that: based on n IABDo :n PCL =1:2 replaced by n IABDO :n PCL =1:4, to obtain itaconic acid polyurethane. By testing its various properties using the same method as above, it was found that the itaconic acid polyurethane had a tensile modulus of 8.9 MPa. The reason is that the component difference ratio between polycaprolactone and itaconic acid oligomer is too large to affect the arrangement of molecular chain segments.

[0122] Comparative Example 4

[0123] The difference between the preparation method of this comparative example and that of Example 1 is that a single itaconic acid oligomer is used instead of a binary soft segment structure to obtain itaconic acid polyurethane. The various properties thereof are tested by the same method as above and it is found that the itaconic acid polyurethane has a tensile modulus of 12.1 MPa, a tensile strength of 18.8 MPa, and an elongation at break of 330%. The mechanical properties are lower than those of Example 1. The reason is that compared with polycaprolactone diol, itaconic acid oligomer has a side double bond structure, which will increase certain steric hindrance and affect the connection and entanglement of the molecular chains.

[0124] Application Examples

[0125] 5 g of the polyurethane film prepared in Example 1 was weighed, cut into pieces and placed in a transparent sample bottle, 9.3 g of DMF was added, and stirred at 70° C. for 2 h to prepare an electrospinning solution with a concentration of 25-35%. The spinning parameters were 10 KV-16 KV voltage range, 0.9-1 ml / h flow rate, 285 rpm receiver drum speed, 15-20 cm spinning receiving distance, and a vascular transplant tubular was prepared.

[0126] In addition, the inventors of this case also conducted experiments with other raw materials and conditions listed in this specification in accordance with the methods of the aforementioned embodiments, and also produced degradable medical itaconic acid polyurethane materials with degradable properties, excellent mechanical properties, stable thermodynamics and good biocompatibility.

[0127] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0128] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A degradable medical itaconic acid polyurethane material, characterized in that: The degradable medical itaconic acid polyurethane material has a structure as shown in formula (I): Wherein, R1 is the residue of a hydroxyl-terminated itaconic acid diol oligomer, R2 is the residue of a polyester diol, D is the residue of a diisocyanate, B is the residue of a linear diol, and n is a positive integer between 5 and 12.

2. The degradable medical itaconic acid polyurethane material according to claim 1, characterized in that: The R1 is a residue of an itaconic acid diol oligomer prepared from itaconic acid and a short-chain diol; preferably, the short-chain diol includes any one of 1,2-ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, and 1,6-hexanediol, or a combination of two or more thereof; And / or, the polyester diol includes any one or a combination of two or more of polycaprolactone diol, polyethylene glycol, and polyhexamethylene adipate; And / or, the number average molecular weight of the polyester diol is 500-2000.

3. The degradable medical itaconic acid polyurethane material according to claim 1, characterized in that: The linear diol includes any one or a combination of two or more of 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, and 1,6-hexanediol; And / or, the diisocyanate includes any one or a combination of two or more of diphenylmethane diisocyanate, isophorone diisocyanate, p-phenylene diisocyanate, 1,5-naphthalene diisocyanate, toluene diisocyanate and dicyclohexyl diisocyanate.

4. The degradable medical itaconic acid polyurethane material according to claim 1, characterized in that: The degradable medical itaconic acid polyurethane material comprises a soft segment comprising residues of itaconic acid diol oligomers and residues of polyester diols, and a hard segment comprising residues of diisocyanate and residues of linear diols; preferably, the content of the soft segment in the degradable medical itaconic acid polyurethane material is 50-70wt%; preferably, the mass proportion of itaconic acid diol oligomers in the soft segment is 25%-65%; And / or, the tensile modulus of the degradable medical itaconic acid polyurethane material is 5 to 80 MPa, the tensile strength is 8.0 to 33.8 MPa, and the elongation at break is 170 to 500%.

5. A method for preparing a degradable medical itaconic acid polyurethane material, characterized in that: include: subjecting a first mixed reaction system comprising itaconic acid, a short-chain diol, a polymerization inhibitor and a first catalyst to an esterification reaction and a polycondensation reaction to obtain a hydroxyl-terminated itaconic acid diol oligomer; A second mixed reaction system comprising itaconic acid diol oligomer, polyester diol, diisocyanate, solvent and a second catalyst is subjected to microwave prepolymerization reaction, and then a linear diol is added to continue the chain extension reaction to obtain a degradable medical itaconic acid polyurethane material.

6. The preparation method according to claim 5, characterized in that: The short-chain diol includes any one or a combination of two or more of 1,2-ethylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 1,5-pentanediol, and 1,6-hexanediol; And / or, the polymerization inhibitor includes any one of 4-methoxyphenol, hydroquinone, o-methyl hydroquinone, and p-hydroxyanisole, or a combination of two or more thereof; And / or, the first catalyst comprises any one or a combination of two or more of stannous chloride dihydrate, p-toluenesulfonic acid hydrate, and zinc acetate dihydrate; and / or, the molar ratio of itaconic acid to short-chain diol is 1:1.1 to 1:1.3; and / or, the amount of the polymerization inhibitor is 0.4-0.8% of the molar amount of itaconic acid; and / or, the amount of the first catalyst used is 0.1 to 0.3% of the molar amount of itaconic acid; And / or, the temperature of the esterification reaction is 120-150° C., and the time of the esterification reaction is 8-10 hours; And / or, the temperature of the polycondensation reaction is 170-180° C., and the time of the polycondensation reaction is 1-4 hours.

7. The preparation method according to claim 5, characterized in that: The polyester diol includes any one of polycaprolactone diol, polyethylene glycol, and polyhexamethylene adipate or a combination of two or more thereof; and / or the number average molecular weight of the polyester diol is 500 to 2000; And / or, the diisocyanate includes any one or a combination of two or more of diphenylmethane diisocyanate, isophorone diisocyanate, p-phenylene diisocyanate, 1,5-naphthalene diisocyanate, toluene diisocyanate and dicyclohexyl diisocyanate; And / or, the linear diol includes any one or a combination of two or more of 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, and 1,6-hexanediol; and / or, the solvent comprises N,N-dimethylformamide; And / or, the second catalyst comprises an amine compound and / or an organic metal compound, preferably any one of dibutyltin dilaurate, stannous octoate, and tin isooctanoate, or a combination of two or more thereof; and / or, the molar ratio of the itaconic acid diol oligomer to the polyester diol is 1:2 to 2:1; and / or, the amount of the second catalyst used is 1% to 2% of the total mass of the second mixed reaction system; and / or, the mass ratio of the combination of the linear diol and the diisocyanate to the combination of the itaconic acid diol oligomer and the polyester diol is 5:5 to 7:3; and / or, the amount of the diisocyanate is calculated based on the hydroxyl groups of the mixture of itaconic acid diol oligomer, polyester diol and linear diol, and the isocyanate index is 1.05 to 1.10; And / or, the temperature of the microwave prepolymerization reaction is 60-70° C., and the time of the microwave prepolymerization reaction is 20-40 min; And / or, the temperature of the chain extension reaction is 60-80° C., and the time of the chain extension reaction is 40-70 min.

8. A degradable medical itaconic acid polyurethane material prepared by the preparation method according to any one of claims 5 to 7.

9. Use of the degradable medical itaconic acid polyurethane material according to any one of claims 1 to 4 and 8 in the preparation of medical implants, preferably, the medical implants include vascular graft tubulars.

10. A method for preparing a vascular transplant tubular article, characterized in that: include: The degradable medical itaconic acid polyurethane material according to any one of claims 1 to 4 and 8 is prepared by electrospinning technology to obtain a vascular transplant tubular object; Preferably, the process conditions of the electrospinning technology include: a spinning solution concentration of 20-30%, a voltage of 12-17 KV, a receiver distance of 12-18 cm, and an injection rate of 0.8-1.2 mL / h.

Citation Information

Patent Citations

  • Novel degradable polyurethane biological material as well as preparation method and application thereof

    CN107686546A

  • Polyurethane elastomer taking bio-based amorphous multi-component polyester as soft segment and preparation method thereof

    CN113121786A

  • Polyurethane type UV viscosity-reducing adhesive and preparation method thereof

    CN113736420A

  • Itaconic acid-based self-repairing polyurethane containing dynamic disulfide bonds as well as preparation method and application of itaconic acid-based self-repairing polyurethane

    CN116515075A

  • Method for synthesis and modification of bio-based polyamide

    US20220332891A1